Measuring the Urban Metropolitanization of Kedungsepur Based on Polycentricity and Spatial Transformation - Indrayati, Ariyani; Rijanta, Rijanta; Muta’ali, Luthfi; Rachmawati, Rini (Jurnal Pembangunan Wilayah dan Kota, 2024)
Kedungsepur, situated in Central Java Province, Indonesia, encompasses the regions of Kendal, Demak, Ungaran, Semarang, Salatiga, and Purwodadi, making it a strategically significant area. Its designation as a metropolitan area was established by Presidential Decree Number 78 of 2017, with one of its primary objectives being to promote equity by reducing urban primacy. This study seeks to assess the metropolitanization of Kedungsepur from 2016 to 2020, focusing on two key indicators: polycentricity and spatial transformation. Polycentricity is evaluated based on concentration, accessibility, and connectivity, while spatial transformation is measured by analyzing the percentage of built-up land and urban level. Polycentricity is assessed using secondary data from BPS-Statistics Indonesia, while the percentage of built-up land and urban level is determined through the interpretation of Sentinel 2A satellite imagery from 2016 and 2020. The findings indicate a moderate improvement in polycentricity during the 2016—2020 period, with partial spatial transformation occurring, particularly along highway corridors between cities. In conclusion, metropolitanization demonstrates positive progress toward its objectives, albeit requiring more balanced control over spatial transformation processes.